A UNIÃO POLIAFETIVA: A FAMÍLIA NA PERSPECTIVA SÓCIO-HISTÓRICA E JURÍDICA - Tinoco Boechat, Ieda; Lacerda Tinoco Boechat Cabral, Hildeliza; Henrique Medeiros de Souza, Carlos; Castro Manhães, Fernanda (LINKSCIENCEPLACE, 2026)
Historically, contemporary society witnesses changes in family compositions in na ever new way. This study, therefore, deals with the family from a juridical and sociohistorical perspective, as well as illustrates its theoretical propositions through factual situations, pointing out necessary counterpoints to the elucidation of the topic that is being debated, namely, the polyphonic family, which Constitutes in the socio-cultural scenario de facto or legally. The research then seeks to answer the questions: in what way new ways of union of people can raise the family polyphative? This social organization of the family group conforms a new familiar configuration of fact and of right? Through bibliographical research and online newspaper consultations, this study investigates aspects related to the socio-cultural and legal recognition of the poly-family as one more familiar configuration in the present day.